MASQUERADING INSULINOMA: A RARE CASE OF ENDOCRINE TUMOR AND COMPLEX CLINICAL PRESENTATION - Pubalan, Sivasankar; Jeevaraj, Lavanya; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Recurrent hypoglycemia poses a diagnostic challenge, particularly when multiple endocrine disorders are present. Adrenal insufficiency, characterized by deficient cortisol production, impairs glucose homeostasis by reducing gluconeogenesis and increasing insulin sensitivity. Insulinoma, a rare pancreatic β-cell tumor, causes unregulated insulin secretion, leading to symptomatic hypoglycemia. Diagnosis relies on Whipple’s triad and specific biochemical markers, including elevated insulin, C-peptide, and proinsulin levels during fasting. The concurrent presence of insulinoma and adrenal insufficiency is rare and requires a high index of suspicion. CASE A 54-year-old male with type 2 diabetes (on metformin), obstructive sleep apnea, and a history of traditional medicine use presented with recurrent dizziness and documented hypoglycemia. Examination and electrolytes were unremarkable. A short Synacthen test showed an inadequate cortisol response, confirming adrenal insufficiency. He was started on oral hydrocortisone, with subsequent stabilization of glucose levels and was discharged. Three months later, he presented again with symptomatic hypoglycemia (as low as 1.2 mmol/L) despite compliance with medications. Biochemical tests revealed elevated insulin (296 pmol/L) and C-peptide (2,595 pmol/L), suggesting endogenous hyperinsulinemia. A 72-hour fast confirmed persistent hypoglycemia with inappropriately high insulin and C-peptide levels. CT imaging showed a distal pancreatic lesion consistent with insulinoma and he then underwent distal pancreatectomy. Hypoglycemia resolved after surgery. He remains stable on hydrocortisone (10 mg three times daily). CONCLUSION This case highlights the rare coexistence of insulinoma and adrenal insufficiency. Cortisol deficiency can obscure insulinoma symptoms, emphasizing the need for a thorough and systematic diagnostic approach to recurrent hypoglycemia.